mRNA circularization by METTL3-eIF3h enhances translation and promotes oncogenesis - Choe, Junho (Nature, 2018)
N(6)-Methyladenosine (m(6)A) modification of messenger RNA (mRNA) is emerging as an important regulator of gene expression that impacts different developmental and biological processes, and altered m(6)A homeostasis is linked to cancer(1-5). m(6)A is catalyzed by METTL3 and enriched in the 3’ untranslated region (3’ UTR) of a large subset of mRNAs at sites close to the stop codon(5). METTL3 can promote translation but the mechanism and widespread relevance remain unknown(1). Here we show that METTL3 enhances translation only when tethered to reporter mRNA at sites close to the stop codon supporting a mRNA looping mechanism for ribosome recycling and translational control. Electron microscopy reveals the topology of individual polyribosomes with single METTL3 foci found in close proximity to 5’ cap-binding proteins. We identify a direct physical and functional interaction between METTL3 and the eukaryotic translation initiation factor 3 subunit h (eIF3h). METTL3 promotes translation of a large subset of oncogenic mRNAs, including Bromodomain-containing protein 4 (BRD4) that are also m(6)A-modified in human primary lung tumors. The METTL3-eIF3h interaction is required for enhanced translation, formation of densely packed polyribosomes, and oncogenic transformation. METTL3 depletion inhibits tumorigenicity and sensitizes lung cancer cells to BRD4 inhibition. These findings uncover a mRNA looping mechanism of translation control and identify METTL3-eIF3h as a potential cancer therapeutic target.